2015
DOI: 10.1136/bmjopen-2015-007838
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of chest ultrasound for CT-detected radiographic consolidation in hospitalised adults with acute respiratory failure: a systematic review

Abstract: Objectives(1) Summarise chest ultrasound accuracy to diagnose radiological consolidation, referenced to chest CT in patients with acute respiratory failure (ARF). (2) Directly compared ultrasound with chest X-ray.SettingHospitalised patients.ParticipantsStudies were eligible if adult participants in respiratory failure underwent chest ultrasound to diagnose consolidation referenced to CT. Exclusion: (1) not primary study, (2) not respiratory failure, (3) not chest ultrasound, (4) not consolidation, (5) transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Lung ultrasound has several advantages over traditional radiography, including the ability to rapidly obtain several views of a particular segment or lobe of lung as well adjacent organs; it avoids transporting patients to radiographic imaging suites which is costly and inconvenient; it can differentiate lung consolidation from pleural effusion with high accuracy; and allows physicians to monitor disease states serially with repeat evaluation performed at the discretion of the investigator. Lung ultrasonography has been shown to be a superior diagnostic method compared to chest radiography, as shown in several published meta-analyses [3234]. In our study, the in-vivo lung ultrasonography had a perfect correlation with the pathological findings identified at the time of necropsy.…”
Section: Discussionsupporting
confidence: 73%
“…Lung ultrasound has several advantages over traditional radiography, including the ability to rapidly obtain several views of a particular segment or lobe of lung as well adjacent organs; it avoids transporting patients to radiographic imaging suites which is costly and inconvenient; it can differentiate lung consolidation from pleural effusion with high accuracy; and allows physicians to monitor disease states serially with repeat evaluation performed at the discretion of the investigator. Lung ultrasonography has been shown to be a superior diagnostic method compared to chest radiography, as shown in several published meta-analyses [3234]. In our study, the in-vivo lung ultrasonography had a perfect correlation with the pathological findings identified at the time of necropsy.…”
Section: Discussionsupporting
confidence: 73%
“…A recent review of the literature suggests that USS is more sensitive than CXR for detection of consolidation [44]. However, differentiating between potential aetiologies (such as pneumonia and pulmonary embolism) is heavily dependent on clinical evaluation and suspicion.…”
Section: Future Directionsmentioning
confidence: 99%
“…Also, some reviews meta-analysed by patient and others by hemithorax. We have previously found that using different units of analysis can give very different test characteristics [32]. …”
Section: Pneumothoraxmentioning
confidence: 99%
“…A recent systematic review examined the accuracy of ultrasound for consolidation referenced to CT (table 3) [32]. This review focused on the imaging findings of consolidation rather than the underlying aetiology.…”
Section: Lung Consolidationmentioning
confidence: 99%
See 1 more Smart Citation